The Squirrel’s Heartbeat - Michelle M. Taylor (Humanimalia, 2020)
Ivan Kreilkamp, Minor Creatures: Persons, Animals, and the Victorian Novel. Chicago: University of Chicago Press. 240 pp. $90 hb, $30 pb.